Promoting healthy practices among schools and children in rural bangladesh: a randomised controlled trial of skill-based health education - Makiko Omura; Mohini Venkatesh; Ikhtiar Khandaker; Md. Ataur Rahman (BMC Public Health)
Abstract Background Poor child health and hygiene practices are persistent issues in resource-constrained settings, particularly in low-income countries. This study assessed the impact of skill-based health education (SBHE) on school and child hygiene practices in rural Bangladesh. Methods A cluster-randomised-controlled intervention with cross-cutting/factorial design was conducted in 180 randomly selected primary schools, stratified by school type, in Jhenaidah District, Bangladesh. Weekly SBHE sessions were delivered to half of the schools by locally recruited para-teachers for one year. A cross-cutting soap provision treatment was given monthly to half of the SBHE-treatment schools and half of the SBHE-control schools. Treatment assignment was masked to all baseline and endline surveyors. Data were collected at both the school and child levels, with child-level data aggregated at the school level. Outcome measures were grouped into five thematic families. The primary outcome families were school hygiene practice & maintenance, school-aggregated child handwashing and school-aggregated child dentalcare. Utilising the difference-in-differences estimator with seemingly unrelated regression, we estimated the average treatment effect for each family of multiple outcomes. The intervention spillover effect to neighbouring schools along with the time-period effect were also evaluated. The project’s cost-effectiveness was additionally assessed. Results Our findings revealed that SBHE had a positive impact on primary outcomes related to healthy practices and behavioural changes, resulting in a 0.32SD improvement in school hygiene practices and maintenance (p < 0.001), a 0.47SD increase in child handwashing (p < 0.001), and a 0.43SD enhancement in child dentalcare (p < 0.01). Despite its imperfect implementation, the provision of soap itself showed no significant effect. Furthermore, significant spillover effects of healthy practices were observed in neighbouring non-treatment schools. The cost-effectiveness analysis indicated that our SBHE program was cost-effective. Conclusions Our study provides compelling evidence of the positive impact of SBHE on school hygiene and child health practices in rural Bangladesh, with notable spillover effects. The cost-effectiveness analysis underscores the value of SBHE, affirming its potential as an effective intervention method in improving school health and hygiene practices in primary schools and beyond.